Methylene blue phosphoramidite for DNA labelling1. Issue 21 (14th March 2015) - De Crozals, Gabriel; Farre, Carole; Sigaud, Monique; Fortgang, Philippe; Sanglar, Corinne; Chaix, Carole
<x xml:space="preserve">Abstract</x> We report the first synthesis of a methylene blue (MB) phosphoramidite derivative suitable for DNA solid-phase synthesis.